2007
DOI: 10.1101/gad.1548107
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human GINS complex

Abstract: The GINS complex mediates the assembly of the MCM2-7 (minichromosome maintenance) complex with proteins in a replisome progression complex. The eukaryotic GINS complex is composed of Sld5, Psf1, Psf2, and Psf3, which must be assembled for cell proliferation. We determined the crystal structure of the human GINS complex: GINS forms an elliptical shape with a small central channel. The structures of Sld5 and Psf2 resemble those of Psf1 and Psf3, respectively. In addition, the N-terminal and C-terminal domains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 22 publications
4
64
0
Order By: Relevance
“…Since archaeal GINS complexes resemble their eukaryotic counterparts in architecture (29), the possibility exists that SsoGINS binds DNA in the same manner. Crystallographic and electron microscopic studies on eukaryotic GINS have revealed various sizes for the central channel, raising the possibility that the protein complex is flexible in structure to permit changes under various conditions (8,42,(45)(46)(47). Therefore, it may be speculated that SsoGINS is capable of undergoing conformational changes upon binding to DNA or when passing DNA into its central channel.…”
Section: Discussionmentioning
confidence: 99%
“…Since archaeal GINS complexes resemble their eukaryotic counterparts in architecture (29), the possibility exists that SsoGINS binds DNA in the same manner. Crystallographic and electron microscopic studies on eukaryotic GINS have revealed various sizes for the central channel, raising the possibility that the protein complex is flexible in structure to permit changes under various conditions (8,42,(45)(46)(47). Therefore, it may be speculated that SsoGINS is capable of undergoing conformational changes upon binding to DNA or when passing DNA into its central channel.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, rotary-shadowed electron microscopic images of the Xenopus GINS complex revealed ring-like structures (7). Furthermore, recent structural studies showed that the crystal structures of the human GINS complex resemble a trapezoid (36) or elliptical shape (37,38), in which the four subunits interact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…As this work was being reviewed, another study reporting the GINS complex structure with truncated Psf1 by Choi et al was published (19).…”
Section: Methodsmentioning
confidence: 99%